Measures on Women's Political Activity During the Years of Independence - Qoraboyeva Dilfuzaxon Qodirjonovna (Central Asian Journal of Theoretical and Applied Science, 2022)
Today, raising the status of women in society, ensuring gender equality and equalizing the rights of women and men in all areas has become one of the most pressing issues. This article discusses in detail one of the most pressing issues, which is the measures taken by women during the years of independence.